A Comparison of Dexmedetomidine and Midazolam for the Prevention of Postoperative Nausea and Vomiting Caused by Hemabate in Cesarean Delivery: A Randomized Controlled Trial - Hu B; Zhou H; Zou X; Shi J; Li X; Tan L (Dove Medical Press, 2020)
Bailong Hu,1,* Haiyan Zhou,2,* Xiaohua Zou,1 Jing Shi,1 Xingyu Li,1 Li Tan1 1Department of Anesthesiology, The Affiliated Hospital of Guizhou Medical University, Guiyang,People’s Republic of China; 2Department of Clinical Research Centre, The Affiliated Hospital of Guizhou Medical University, Guiyang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bailong Hu Email 375896605@qq.comObjective: To compare the efficacy of dexmedetomidine and midazolam in the prevention of postoperative nausea and vomiting (PONV) caused by hemabate in postpartum hemorrhage during cesarean delivery.Methods: One hundred and five parturients with American Society of Anesthesiology (ASA) physical status I and II, aged 20– 40 years, undergoing elective cesarean delivery under epidural anesthesia were randomly allocated into dexmedetomidine group (group D, n=35), midazolam group (group M, n=35) and control group (group C, n=35). Patients received an intrauterine injection of 250 μg hemabate and continuous intravenous infusion of 5 units oxytocin immediately following the delivery of the infant. At the same time, patients in group D received 1μg/kg intravenous dexmedetomidine, group M received 0.02 mg/kg intravenous midazolam and group C received 20 mL intravenous saline. Parameters such as the PONV, other adverse reactions (chest distress, flush, etc.) caused by hemabate, patient satisfaction, the sedation (OAA/S) scores, and the hemodynamic parameters were recorded in both groups.Results: The PONV incidence in group D and group M was significantly lower compared with group C (6%, 17%, and 71% for group D, group M, and group C, respectively, P< 0.05). The sedation (OAA/S) scores in group D and group M was significantly higher compared with group C (1.62± 0.28, 1.75± 0.31, and 1.00± 0.00 for group D, group M, and group C, respectively, P< 0.05). The patient satisfaction in group D and group M was significantly higher compared with group C (94%, 69%, and 46% for group D, group M, and group C, respectively, P< 0.05). Furthermore, there were more patients satisfied with group D than group M (94% vs.69%, P< 0.05).Conclusion: Intravenous dexmedetomidine (1 μg/kg) and midazolam (0.02 mg/kg) were equally effective in preventing PONV introduced by hemabate and dexmedetomidine is superior to midazolam in patient satisfaction.Keywords: dexmedetomidine, midazolam, PONV, hemabate, cesarean delivery